Blood-brain barrier dysfunction developed during normal aging is associated with inflammation and loss of tight junctions but not with leukocyte recruitment - Elahy, Mina; Jackaman, Connie; Mamo, John; Lam, V.; Dhaliwal, S.; Giles, C.; Nelson, Delia; Takechi, Ryu (BioMed Central Ltd., 2015)
Background: Functional loss of blood–brain barrier (BBB) is suggested to be pivotal to pathogenesis and pathology of vascular-based neurodegenerative disorders such as Alzheimer’s disease. We recently reported in wild-type mice maintained on standard diets, progressive deterioration of capillary function with aging concomitant with heightened neuroinflammation. However, the mice used in this study were relatively young (12 months of age) and potential mechanisms for loss of capillary integrity were not investigated per se. The current study therefore extended the previous finding to investigate the effect of aging on BBB integrity in aged mice at 24 months and its potential underlying molecular mechanisms. Results: Immunomicroscopy analyses confirmed significantly increased capillary permeability with heightened neuroinflammation in naturally aged 24-month old mice compared to young control at 3 months of age. Aged mice showed significant attenuation in the expression of BBB tight junction proteins, occludin-1 and to lesser extent ZO-1 compared to young mice. In addition, TNF-α in cerebral endothelial cells of aged mice was significantly elevated compared to controls and this was associated with heightened peripheral inflammation. The expression of ICAM-1 and VCAM-1 remained unelevated, and no sign of leukocyte recruitment was observed in aged mice. Conclusion: The BBB breakdown that occurs during ordinary aging is associated with inflammation and disruption of tight junction complex assembly but not through leukocyte trafficking.